An An Educational Coloring Book on North Maluku Endemic Wildlife for Elementary Schools - Ridwan Jusuf; Wawan Suprianto Nadra; Eko Purnomo; Ibrani Gobel; Nurilin (LPPM Undiksha, 2026)
Elementary school students' knowledge of this animal remains low, as reflected in the limited integration of local materials into the curriculum. This study aims to create an educational coloring book with an endemic animal theme for elementary school students as a valid, practical, and effective learning medium. The research method uses a Research and Development (R&D) approach, employing the ADDIE model across the analysis, design, development, implementation, and evaluation stages. The methods used include observation, interviews, questionnaires, and tests. The instruments used include expert validation sheets. The trial subjects involved 37 third-grade students of SD Negeri 40 and 41. Product validity was assessed by material and media experts, practicality through teacher and student questionnaires, and effectiveness through pre-test and post-test comparisons. The results showed a very high level of validity (92.88%), very good practicality among teachers (95.0%) and students (93.0%), and significant effectiveness in increased learning outcomes (p < 0.05; N-gain = 0.58 in the medium category). Thus, this coloring book is feasible, practical, and effective, with the potential to be replicated on biodiversity themes in other regions. This research implies that teachers can utilize this medium to create an interactive and enjoyable learning environment. Furthermore, integrating themes of endemic animals can serve as a means of environmental education and local biodiversity conservation.